TRANSFORMATIONAL LEADERSHIP IN IMPROVING LECTURER PERFORMANCE AT MUHAMMADIYAH HIGHER - Saipul Wakit; Indah Yuliana (Bajang Institute, 2021)
The transformational leadership style in higher education has four indicators carried out by the rector. These indicators include exemplary attitudes, inspiring motivation, intellectual stimulation and the rector's consideration for lecturers. Practically, the purpose of this article is to find out how the rector provides examples, inspires motivation and individual considerations in improving the performance of lecturers at Muhammadiyah universities. The operational research method uses a qualitative approach with a phenomenological case study design. Data collection activities were carried out by means of observation, interviews with informants, and extracting information from documents. To ensure the validity of the research data, several methods are used, namely credibility, transferability, dependability and confirmability. The results of the study explain that transformative leadership in Muhammadiyah universities objectively has provided an example with several things that are applied in attitudes, ideas, behavior and performance. While motivation is carried out by the Chancellor of the lecturers in several ways, namely through behavior, technical ability, supervision and policy. In stimulating the intellectuals of lecturers in several ways, namely to think modern and relevant, think forward and continue to make changes as well as productive, innovative, creative in carrying out tasks and performance. In individual consideration, the Chancellor is more humane towards lecturers, both in the work environment and in the community.